Characteristic example of insulation coordination in power converters - Despotović, Željko V (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
Devices and modules of power electronics that are most often used in power supply systems for various purposes, industrial AC drives and in the field of distributed energy sources in relation to the passive components have a very poor ability to withstand surge voltages. These surge voltages can be of different origins, and in most cases are transient surges, which even when low levels can lead to damage to the mentioned power electronics devices or power converter components. For these reasons, it is very important to implement a number of measures in order to ensure the insulating properties of the entire system, as well as the power converter itself as part of that system. In this paper, based on the adopted standards and relevant literature, characteristic examples and insulation coordination solutions for two representative types of power converters are given: industrial AC drive and photovoltaic inverter used in solar “on-grid” power systems.
Keywords: insulation coordination, power converter, AC drive, PV inverter, PELV